Dynamic Stiffness Analysis Of Engine Rubber Mounts - Ooi , Lu Ean (2010)
Dynamic stiffness and loss factor for engine rubber mount are important dynamic behaviour to represent the performance of an engine mount system. Damping and dynamic stiffness measurement play important role in the characterization of dynamic properties for the engine rubber mount system. Impact test is simple and powerful measurement technique for damping measurement. The recent development of impact technique is the application on dynamic driving point stiffness measurement. In this thesis, the impact technique is further developed for dynamic transfer stiffness measurement where the impact hammer is used to replace shaker as the source of excitation in damping measurement. The mathematical formulation and the experimental procedures to measure dynamic driving point stiffness and dynamic transfer stiffness for engine rubber mount by using impact test are presented. The results showed that the dynamic driving point stiffness can only be used to represent dynamic transfer stiffness for the lower range of frequency. The mass between the test isolator and the input force transducer will influence this range of frequency. The loss factor of the engine mount is also estimated in the function of frequency. The curve fitted function of loss factor (η11) showed linear dependency of the engine rubber mount system on the frequency and loss factor (η21) showed non-linear dependent of the resilient element on the frequency. By using this curve fitted loss factor, the dynamic driving point stiffness and dynamic transfer stiffness are accurately reproduced and compared to the measured results. The results obtained by using the impact technique are finally validated with the results obtained by using shaker.